Depression symptom severity and behavioral impairment in school-going adolescents in Uganda - Ronald Anguzu; Catherine Abbo; Julia Dickson-Gomez; Max Bobholz; Arthur Kiconco; Abdul R. Shour; Richard Kabanda; Kenneth Kalani; Laura D. Cassidy (BMC Psychiatry)
Abstract Background During adolescence, a critical developmental phase, cognitive, psychological, and social states interact with the environment to influence behaviors like decision-making and social interactions. Depressive symptoms are more prevalent in adolescents than in other age groups which may affect socio-emotional and behavioral development including academic achievement. Here, we determined the association between depression symptom severity and behavioral impairment among adolescents enrolled in secondary schools of Eastern and Central Uganda. Methods This cross-sectional study was conducted among 1,669 adolescents enrolled in secondary schools in Eastern and Central Uganda. Our outcome variable was behavioral impairment defined as self-reported behavior that interferes with an individuals’ ability to do schoolwork (school performance) or get along with others (peer interaction) (yes/no). The key independent variable was depression symptom severity assessed using the Child and Adolescent Symptom Inventory-5 (CASI-5), a behavior rating scale for symptoms of DSM-5 emotional and behavioral disorders. Modified Poisson regression models tested the independent association between depressive symptom severity and behavioral impairment. Prevalence Rate Ratios (PRR) and 95% confidence intervals (95%CI) were reported. Results Participants’ mean age was 15.3 years (SD = 1.8), 58.5% were female, 86.8% witnessed domestic violence, 47.4% had behavioral impairment, and 2.8% had mild depression symptoms. School-going adolescents with mild depression symptoms had two times higher risk of behavioral impairment when compared to those with no or slight depression symptoms, after controlling for potential confounders. Other factors independently associated with higher risk for behavioral impairment were female sex (Adj. PRR 1.27, 95%CI 1.12, 1.43) compared to males, taking alcohol (Adj. PRR 1.42, 95%CI 1.25, 1.61) compared to not taking alcohol, boarding school enrollees (Adj. PRR 1.62, 95%CI 1.33, 1.98), and day school enrollees (Adj. PRR 1.46, 95%CI 1.21, 1.76) compared to mixed (day and boarding) school enrollees respectively, advanced level enrolment (Adj. PRR 1.25, 95%CI 1.05, 1.48) compared to ordinary level enrolment, and attending urban schools (Adj. PRR 1.27, 95%CI 1.11, 1.45) compared to rural secondary school attendance. Conclusions Behavioral impairments are widespread among Ugandan secondary students. Mild depression symptoms adversely affect adolescents' academic and social lives, potentially leading to long-term consequences. Where feasible, early detection of depressive symptoms and treatment may mitigate their negative effects on student school performance ability and peer/social interaction. Future research should examine school-level factors influencing academic performance by depression status. Policymakers in education and gender sectors should prioritize mental health programs in secondary schools.